2021
DOI: 10.1051/0004-6361/202141647
|View full text |Cite
|
Sign up to set email alerts
|

Evolution patterns of the peak energy in the GRB prompt emission

Abstract: Context. The peak energy (Ep) exhibited during the prompt emission phase of gamma-ray bursts (GRBs) shows two different evolution patterns, namely hard-to-soft and intensity-tracking, of which the physical origin remains unknown. In addition to low-energy indices of GRB prompt spectra, the evolution patterns of Ep may be another crucial indicator with which to discriminate radiation mechanisms (e.g., synchrotron or photosphere) for GRBs. Aims. We explore the parameter space to find conditions that could genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 102 publications
2
4
0
Order By: Relevance
“…However, increased central-engine activity during the bursting phase might increase the magnetic field, resulting in a higher E p and/or intensity. If such a scenario is true, the magnetic field should be strongly correlated with E p (Gao et al 2021). Interestingly, we found a strong correlation between E p (derived using the empirical Band function) and the magnetic field B (derived using the physical Synchrotron model), supporting our results discussed above.…”
Section: Discussionsupporting
confidence: 89%
“…However, increased central-engine activity during the bursting phase might increase the magnetic field, resulting in a higher E p and/or intensity. If such a scenario is true, the magnetic field should be strongly correlated with E p (Gao et al 2021). Interestingly, we found a strong correlation between E p (derived using the empirical Band function) and the magnetic field B (derived using the physical Synchrotron model), supporting our results discussed above.…”
Section: Discussionsupporting
confidence: 89%
“…A small fraction of bursts also exhibit the behavior of "E p tracking the flux" rather than the hard-to-soft pattern (e.g., Lu et al 2012), implying that additional effects should be taken into account. These effects can include the acceleration of the emitting region (Uhm & Zhang 2015Uhm et al 2018;Gao et al 2021) and the synchrotron self-Compton process (Zhao et al 2014;Geng et al 2018;Gao et al 2021). Our findings demonstrate that at least for some bursts, synchrotron radiation alone can serve as a dominant factor and consistently reproduce the observed E p evolution.…”
Section: E P Evolutionsupporting
confidence: 54%
“…The evolution pattern of E p may be another indicator to identify the mechanism of GRB radiation. In the framework of synchrotron emission, Gao et al (2021) described the evolution of electrons and the corresponding synchrotron emission by numerical methods to explore the evolution mode of E p . They found that when a spherical shell moves with a constant bulk Lorentz factor, and the electrons are dominated by adiabatic cooling or adiabatic synchrotron self-Compton (SSC) cooling, a trend of E p tracking flux may appear; when the spherical shell is accelerated as a whole, the electrons are dominated by SSC cooling and can be cooled at 10 14 cm.…”
Section: Summary and Discussionmentioning
confidence: 99%